KEMAMPUAN BERPIKIR KRITIS MATEMATIS DIKAJI DARI STUDENTS BELIEF DALAM MATERI SPLDV DI SMP - Febriano, Rionald; Sugiatno, Sugiatno; Suratman, Dede (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe fact that studentsâ€™ mathematical critical thinking ability are low. Critical thinking are influenced by some factors, one of them is belief. This research aimed to explorate the mathematical critical thinking ability assessed from the students' belief in solving systems of linear equations in two variable materials. The research method was descriptive in form of case study. Subjects in this research are eight students at SMP Negeri 24 Pontianak. The results of this research indicated that students' mathematical critical thinking ability variation depend on their beliefs. Students who have the highest mathematical critical thinking ability are students with belief in following the learning process and usefulness of mathematics. Students who have the lowest mathematical critical thinking ability are students with belief in the usefulness of mathematics. On the other hand, students with belief in self-ability when study mathematics have mathematical critical thinking ability with medium category.Â Keywords: Mathematical Critical Thinking Ability, Students Belief, System of Linear EquationsÂ